Mixed convection flow of hybrid nanofluid through a vented enclosure with an inner rotating cylinder. (February 2021) - Jasim, Laith M.; Hamzah, Hudhaifa; Canpolat, Cetin; Sahin, Besir
Abstract: A numerical solution for the influence of an inner adiabatic rotating cylinder inside a vented cavity on mixed convection of hybrid nanofluid is presented in this study. The governing equations of mixed convection flow for an incompressible Newtonian hybrid nanofluid are assumed to be two-dimensional, steady, and laminar. These equations are solved numerically by using the finite volume technique. In this work, (Al2 O3 –Cu / water ) is introduced as a hybrid nanofluid . The influences of relevant parameters including nanoparticle concentrations (0 ≤  φ 1  ≤ 0.02 and 0 ≤  φ 2  ≤ 0.02), cylinder radiuses (0.1 ≤  R  ≤ 0.3), cylinder locations (0.25 ≤  δ  ≤ 0.75), angular rotational speeds (−5 ≤ Ω ≤ 5), Grashof numbers (10 3  ≤  Gr  ≤ 10 5 ) and Reynolds numbers (50 ≤   Re   ≤ 500) are examined. The obtained data are exhibited by means of different qualitative and quantitative figures. The results show that the energy transport of hybrid nanofluid enhances with an increase in solid particle concentration, but it is associated with an increased pressure drop. With respect to the stationary cylinder, it is reported that the counter-clockwise cylinder rotation increases convective heat transfer whereas the clockwise direction has a reverse effect. In addition, for the counter-clockwise rotation of the cylinder, the heat transfer enhances when the position of the cylinder approaches the hot wall. The maximum heat transfer enhancement over the stationary cylinder with 21% occurs in case of R  = 0.3 and δ = 0.5 under Gr  = 104, φ 1 =  φ 2 = 0.02, Re  = 100 and Ω =5. The current study can provide useful guidelines to the designers of rotary heat exchangers.